The Routledge handbook of the Crimean War
1 online resource
Keywords: "The Routledge Handbook of the Crimean War is an edited collection of articles on the various aspects of the Crimean War written by distinguished historians from various countries. Part I focuses on diplomatic, military and regional perspectives. Part II includes contributions on social, cultural and international issues around the war. All contributions are based upon findings of the latest research. While not pretending to be an exhaustive encyclopaedia of this first modern war, the present volume captures the most important topics and the least researched areas in the historiography of the war. The book incorporates new approaches in national historiographies to the war and is intended to be the most up-to-date reference book on the subject. Chapters are devoted to each of the belligerent powers and to other peripheral states that were involved in one way or another in the war. The volume also gives more attention to the Ottoman Empire, which is generally neglected in European books on the war. Both the general public and students of history will find the book useful, balanced and up-to-date"--